Minat Siswa Kelas XI SMA Negeri 8 Padang Terhadap Pembelajaran Seni Musik Melalui Metode Drill - Rezky Dekmo; Ardipal Ardipal (FBS Universitas Negeri Padang, 2021)
This research aims to find out the interest of grade XI students of SMA 8 Padang towards music learning through drill method. This is a quantitative research and described with descriptive statistics. The population in this study was grade XI students of SMA N 8 Padang consisting of 9 classes, 5 classes majoring in MIA (IPA) and 4 classes majoring IPS. The instrument used was a questionnaire. The data collection techniques were performed by disseminating questionnaires and returning questionnaires. The data analysis was conducted by using precentase formulas. The results show that the attention of grade XI students of SMA 8 Padang towards music learning activities by using drill method is classified High with a percentage of 78.98%. The students’ interest towards music learning activities by using Drill method is categorized high with a percentage of 74.97%. The willingness of grade XI students of SMA 8 Padang towards music learning activities using the Drill method belongs to the high category, with a percentage of 77.92%. Overall, the interest of grade XI students of SMA 8 Padang towards music learning using the Drill method is High with a percentage of 77.29%.